Green Competitive Advantage Moderate:Environmental Performance, Corporate Image And Corporate Social Performance On Economic Performance - Eksandy, Arry; Murtanto; Regina J. Arsjah (International Journal of Science, Technology & Management, 2021)
This research aims to determine the effect of environmental performance, corporate image, and corporate social performance on economic performance with moderated by green competitive advantage partially on manufacturing companies in Indonesia. The population in this research is all manufacturing companies listed on Indonesia Stock Exchange during the period 2013-2017. The total samples tested were 13 companies selected by purposive sampling technique. Data type in this research use secondary data obtained from Indonesia Stock Exchange and site respectively of company being sampled. Data analysis technique use panel data regression with Eviews 9.0 program. The result indicates that environmental performance have a positive effect on economic performance and after moderated by green competitive advantage of environmental performance has a positive effect on economic performance with a larger coefficient value. Corporate image have no effect on economic performance but after moderated by green competitive advantage of Corporate image has a positive effect on economic performance. Corporate social performance have no effect on economic performance and after moderated by green competitive advantage of Corporate image also has not effect on economic performance.